Legal Protection To Buyers Through PPJB Condotel - suwardi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The development of a residential property in business so attractive to operators property so that growth is very fast. Accompanied the population growth of it so dwelling that is required quite big so very interesting to handle market by developers because it very promising the property business.The purpose of this study is how the legal protection for condotel buyers using PPJB. This research method uses a normative legal study method that includes writing through the norms published in laws and regulations relating to regulations in the legal process and costs that lead to the implementation of buying and selling through PPJB. with the provisions of the Constitution number 20 of 2011 is expected to be in accordance with the applicable provisions. Results The responsibility of the payment of scope to make good the loss for business operators, namely a. demands based on defaults; and b. demands by all accounts unlawfully if it is associated Loss to the scope of their responsibilities, so any change to the hotel operator in the sphere of responsibility.